1997
DOI: 10.1037/0735-7044.111.3.633
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory functions, sodium appetite, and conditioned taste aversion survive excitotoxic lesions of the thalamic taste area.

Abstract: Rats with bilateral, electrophysiologically guided, ibotenic acid lesions of the gustatory thalamus (THLX) were tested for their ability to perform a variety of taste-guided behaviors. First, in daily 30-min sessions, the rats were given repeated 10-s access periods to a range of concentrations of sucrose, NaCl, or QHCl, plus water. Both the control and the THLX rats exhibited similar concentration-response functions, regardless of hydrational state. Next, on 3 trials, the rats were given 15 min access to 0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 50 publications
6
68
1
Order By: Relevance
“…The suppressive effects of cocaine and sucrose, but not LiCl, are augmented in rats with a history of chronic morphine treatment [57]. Finally, bilateral lesions of the gustatory thalamus or gustatory cortex disrupt the suppressive effects of morphine, cocaine, and sucrose, but have no impact on the development of a LiCl-induced CTA [58][59][60][61][62][63][64][65]. Taken together, the data confirm that drug-induced suppression of CS intake is not mediated by a conditioned taste aversion like that induced by the aversive agent.…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppressive effects of cocaine and sucrose, but not LiCl, are augmented in rats with a history of chronic morphine treatment [57]. Finally, bilateral lesions of the gustatory thalamus or gustatory cortex disrupt the suppressive effects of morphine, cocaine, and sucrose, but have no impact on the development of a LiCl-induced CTA [58][59][60][61][62][63][64][65]. Taken together, the data confirm that drug-induced suppression of CS intake is not mediated by a conditioned taste aversion like that induced by the aversive agent.…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 99%
“…They seek to satisfy this need state much as they seek food when hungry, water when thirsty, and salt when sodium deficient [65]. When these biological drive states are activated, there is a single goal and there can be no substitute.…”
Section: Competing Motivations: Closing the 'Window Of Inopportunity'mentioning
confidence: 99%
“…For example, whereas the afferent projections from the PbN to the VPMpc were well documented, the efferent projections from the VPMpc to the PbN were not demonstrated (4,21,64). In addition, while earlier studies have shown that the VPMpc is involved in taste detection and discrimination (32), sodium appetite (30,44), and CTA (37,92,93), more recent studies have demonstrated that the VPMpc has a minimal influence on innate taste preference (15,62,78), sodium appetite (14,65), or CTA (14,65). Thorough reviews of earlier studies suggested that the claim of the involvement of VPMpc in taste preference, sodium appetite, and CTA were derived from the lesions that were misplaced, inordinately large, or destroyed fibers of passage (58,60,69).…”
mentioning
confidence: 94%
“…Some studies have reported that VPMpc-lesioned animals retain a normal concentration response to preferred and non-preferred tastes [134][135][136][137] but may have disrupted [137], impaired [127,130] or else have no effects on CTA [134,135,138,139]. Current views suggest a role in comparing novel and familiar tastes [140] in more complex gustatory learning tasks or in attention to gustatory function [135,136,141].…”
Section: The Gustatory System In the Ratmentioning
confidence: 99%